The promise and record of international institutions. (June 2019) - Brown, Chris
In 1919 the attempt was made to reset the institutions governing international relations, with new patterns of expected behaviour and new international organisations. The key organisation, the League of Nations, effectively remains in place, albeit rebranded as the United Nations, but in 2019 great power relations have reverted to pre-1914 modes of conduct; attempts to extend the range of international institutions after the end of the Cold War have failed at the level of the central system. Outside of this central system, an extensive human rights regime, new notions of sovereignty and the development of international criminal law have produced a new set of institutions and expectations, an embryonic 'global polity' based on post-1945 European political experience and extending to democracies in Latin America and Africa. The rise of populism is placing strains on this global polity and the relations between this mode of doing international relations and that of the three major powers is also a source of tension – the fate of the liberal internationalist ideas set in train in 1919 remains in the balance.